Beyond the Perimeter of Depoliticization. The Evolution of the Global Governance of Refugees and its Territorialisation in Calabria - D'Agostino, Mariafrancesca (PARTECIPAZIONE E CONFLITTO, 2017)
This study explores the evolution of the global governance of refugees in light of studies on depoliticisation. Following theories on governmentality, it emphasizes the centrality of the concept of de-politicisation when examining the narratives and practices implemented to establish an extraterritorial asylum system of humanitarian containment, detached from any ideals of inclusion and rehabilitation. At the same time, we recall diverse empirical evidence in order to stress the importance of considering the divergent effects of depoliticisation in geographically and culturally distant contexts. The survey in Ca-labria, Italy, presents in fact the political attempt by its inner areas to foster autonomous practices of in-clusion that contrast the securitarian shift of the global asylum system, as well as its national implications, recognising refugees as a strategic factor of economic growth and social innovation. In particular, we re-veal the mechanisms through which new forms of local citizenship have emerged here, along with institu-tional solutions specifically connoted by a bilateral and place-based approach to forced migration. These efforts persist despite the breakup of the current European refugee crisis which, however, now opens new dilemmas by diminishing the viability of refugee relocation within the internal areas as a truly sustainable process.